Canine morphometrics as a tool for distinguishing species, sex, and age class in Southern Ocean fur seals. (15th November 2022) - Pretorius, Liezl E.; Bester, Marthán N.; Connan, Maëlle; Hofmeyr, G. J. Greg
Abstract: Carcasses resulting from natural mortalities are invaluable for use in scientific studies, provided species, sex, and age class are known. When such data are unavailable, identifying skeletal remains is necessary if one is to use the information contained within samples. Teeth are amongst the best preserved skeletal remains owing to the durability of enamel and dentine. Here, we tested whether external measurements of canines could be used to distinguish two partially sympatric species of Southern Ocean fur seals, the Antarctic Arctocephalus gazella and Sub‐Antarctic A. tropicalis fur seals. We also investigated whether the external measurements of canines could be used to determine the age, sex, as well as island of origin of the animals. Eight morphological variables (crown length, root length, crown width, root width, crown thickness, root thickness, total canine length, and count of external surface annular ridges) were recorded from canines of 340 individuals of known species, sex, and island of origin. The count of external annular ridges provided a good estimate of age, which was confirmed by counting the growth layer groups of sectioned teeth, especially for older animals (> 9 years old). External canine measurements proved useful in distinguishing species, as well as sex within and between species, particularly in adult animals. Species were more difficult to distinguish in females than in males. The islands of origin could only be inferred in male Antarctic fur seals. This study indicates that fur seal teeth of unknown provenance, found either in breeding colonies or as vagrants, provide evidence on species, sex, and age of the animal, which increases the value of associated samples. It further highlights the importance of external measurements of skeletal remains such as canine teeth in separating closely related species. Abstract : Measurement axes taken of Antarctic ( Arctocephalus gazella ) and Sub‐Antarctic ( A. tropicalis ) fur seal teeth: crown length (CL), root length (RL), maximum crown width (CW), and maximum root width (RW) were taken on the lateral aspect (mesial‐distal axis) of the teeth, while maximum crown thickness (CT), maximum root thickness (RT),  and total canine length (TCL) were taken on the anterior aspect (buccal‐lingual axis) (following Lowry and Folk (1990) and Molina‐Schiller and Pinedo (2004b)).